Diketopyrrolopyrrole-based multifunctional ratiometric fluorescent probe and γ-glutamyltranspeptidase-triggered activatable photosensitizer for tumor therapy. Issue 24 (26th May 2020) - Yang, Zhicheng; Xu, Weibo; Wang, Jian; Liu, Lingyan; Chu, Yanmeng; Wang, Yu; Hu, Yue; Yi, Tao; Hua, Jianli
Abstract : An activatable diketopyrrolopyrrole-based photosensitizer targeting tumor-related biomarker γ-glutamyltranspeptidase was developed, in which it showed specific photodynamic killing effect to HepG2 cells. Abstract : Photosensitizers can generate highly reactive oxygen species (ROS) by light excitation, causing cell damage and apoptosis. However, conventional photosensitizers cannot kill cancer cells selectively. In this work, we report a series of diketopyrrolopyrrole (DPP)-based photosensitizers, in which DPP-py with one pyridine group exhibits superior photodynamic killing effect on tumor cells. Furthermore, by introducing 4-bromomethyl-phenyl glutamic acid in DPP-py, we adopt a strategy involving the intramolecular charge transfer effect to develop a multifunctional DPP-based ratiometric fluorescent probe and activatable photosensitizer DPP-GGT, which can target the tumor-related biomarker γ-glutamyltranspeptidase (γ-GT). DPP-GGT shows highly selective and obvious fluorescent changes from red to yellow for γ-GT. More importantly, DPP-GGT exhibits specific photodynamic killing effects on human hepatic cancer cells HepG2 due to the high activity of endogenous γ-GT but no marked phototoxicity toward low-γ-GT-expressing breast cancer cells MCF-7 or normal hepatocyte cells L02. The results demonstrate that DPP-GGT has great potential for the tumor-specific activatable photodynamic anticancer therapy.